2000
DOI: 10.1029/2000jd900308
|View full text |Cite
|
Sign up to set email alerts
|

Daytime HO2 concentrations at Oki Island, Japan, in summer 1998: Comparison between measurement and theory

Abstract: Abstract. The daytime variation of hydroperoxy (HO:) radical concentration was observed by an instrument based on laser-induced fluorescence with NO addition at Oki Island, Japan, in July/August 1998. Although OH was not detected due to the high detection limit of the instrument, HO: was determined with the detection limit of 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 71 publications
4
98
2
Order By: Relevance
“…The agreement between modelled and measured [HO 2 ] is variable. Some studies show a reasonable agreement with the measurements (within 25%), but generally the models tend to overestimate [HO 2 ] by a factor of 2 or more (Carslaw et al, , 2002Kanaya et al, 2000Kanaya et al, , 2001. In PEM Tropics B Tan et al (2001) reported a modelled to observed ratio of 1.12 for HO 2 near the surface.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The agreement between modelled and measured [HO 2 ] is variable. Some studies show a reasonable agreement with the measurements (within 25%), but generally the models tend to overestimate [HO 2 ] by a factor of 2 or more (Carslaw et al, , 2002Kanaya et al, 2000Kanaya et al, , 2001. In PEM Tropics B Tan et al (2001) reported a modelled to observed ratio of 1.12 for HO 2 near the surface.…”
Section: Introductionsupporting
confidence: 52%
“…Table 5. The agreement between the models and the measurements is roughly within a factor of 2 around midday, which is better than was found in previous modelling results for HO 2 (Carslaw et al, , 2001George et al, 1999;Kanaya et al, 2000;Stevens et al, 1997).…”
Section: Oh Measured To Modelled Comparisonscontrasting
confidence: 42%
See 1 more Smart Citation
“…Heterogeneous HO 2 loss constitutes 5-10% of the homogeneous gas-phase chemical loss for low to moderate aerosolloading conditions and becomes comparable to gas-phase chemical loss for high aerosol loading (17,18). These estimates assume that HO 2 is irreversibly destroyed after being accommodated by the aerosol surface, and this assumption remains the principle uncertainty in the process.…”
Section: Discussion and Implications For The Interactions Of Ho 2 Andmentioning
confidence: 99%
“…Numerous previous studies have consistently reported a discrepancy between modelled and observed concentrations of HO 2 in different regions. The overestimation of HO 2 concentrations by the models has been attributed to heterogeneous loss of these radicals on aerosol surface as a missing HO 2 sink, not properly accounted for in the models (Cantrell et al, 1996a, b;Jaeglé et al, 2000;Kanaya et al, 2000;Sommariva et al, 2004Sommariva et al, , 2006de Reus et al, 2005;Mao et al, 2010). The laboratory database for uptake coefficients of HO 2 on different surface types is rather scarce, especially for solid surfaces.…”
Section: Introductionmentioning
confidence: 99%